2022
DOI: 10.1101/2022.08.23.504907
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large-scale proteomic analysis of T. spiralis muscle-stage ESPs identifies a novel upstream motif for in silico prediction of secreted products

Abstract: The Trichinella genus contains parasitic nematodes capable of infecting a wide range of hosts including mammals, birds and reptiles. Like other helminths, T. spiralis secretes a complex mixture of bioactive molecules capable of modulating its immediate surroundings and creating a hospitable environment for growth, survival and ultimately transmission. The constitution of these excretory-secretory products (ESPs) changes depending on the tissue niche and the specific stage of parasite development. Unique to T. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Host-parasite interaction: Secretome analysis of T. spiralis encysted larvae in muscles showed several E/S proteins that are considered as immunomodulators in the host. Nash et al [72] showed that PouStich motif (one of the main pro-regulatory motifs) was associated with many proteins derived from T. spiralis stichosome oesophagus and seemed to master the function of the worm's secretome and facilitate the prediction of proteins secreted throughout T. spiralis lifecycle [72] .…”
Section: Trichinella Spiralismentioning
confidence: 99%
“…Host-parasite interaction: Secretome analysis of T. spiralis encysted larvae in muscles showed several E/S proteins that are considered as immunomodulators in the host. Nash et al [72] showed that PouStich motif (one of the main pro-regulatory motifs) was associated with many proteins derived from T. spiralis stichosome oesophagus and seemed to master the function of the worm's secretome and facilitate the prediction of proteins secreted throughout T. spiralis lifecycle [72] .…”
Section: Trichinella Spiralismentioning
confidence: 99%